Sistema de informação do pré-natal do município de Vitória, ES : avaliação da qualidade e indicadores da assistência - Maia, Vivian Kecy Vieira (2016)
Introduction: An Information System is characterized as a set of organized procedures that has the aim of delivering information between people, departments and institutions, and it becomes significant to know its quality. The pre-natal clinical form also serves as data source for entering information in the Pre-natal Monitoring System (SISPRENATAL) of the Health Department, and it allows evaluating the process indicators for the Prenatal and Birth Humanization (PHPN) and the Rede Cegonha Programs. Objectives: To evaluate the quality of a pre-natal information system; to analyse the process indicators of the Prenatal and Birth Humanization and Rede Cegonha Programs from the Pre-natal information system; and to update the information system for the pre-natal visits.